An Industrial system design study on Beaute Mondiale - Sarmeinto, Wilburt (Diliman, Quezon City College of Engineering, 2005)
Beaute Mondiale is a start-up, direct seller of beauty product, implementing the MLM-Hybrid System. It was founded on Dec 18, 2004 and is currently experiencing strategic deficiencies which are preventing it from overcoming the various barriers to entry in the industry. Through Industry and Competitor Analysis for Beaute Mondiale, it was established that continued efforts by the Beaute Mondiale Company to penetrate the beauty industry is promising. This is with due consideration to the healthy state of the industry and the competiveness of the company in the areas of price and quality. With the established company vision and missions in mind, three urgent and immediate goals were established based on the company's current position and urgent needs. These goals are: Generate Revenue Immediately, Maximize Customer Satisfaction, and Stream Line System Processes. Analysis of the company's existing strategies to address these goals showed key areas of weaknesses and poor performances in the areas of recruitment, sales and internal systems. Utilizing strategic management tools, namely, the SWOT Analysis, TOWS Matrix and Porter's 5 Forces, key potential strategies were developed. The top 6, based on value engineering ranking, with consideration their congruence with the vision, mission and goals, were identified. These include: Liquidate Inventory Immediately, Strengthen and Empower Existing Sales Force, Focus Restructure and Formalize Sales Telemarketing, Focus on Quality Efforts, Focus on System Stability efforts and Implement a Buy Back Policies similar to those implemented by all DSAP (Direct Selling Association of the Philippines) members. Further discussion of these strategies, with focus on their strengths, weaknesses, and consideration to their interaction with opportunities and threats, exposed their ability or inability to overcome the strategic gaps. The top 3 of these strategies, based on the value engineering conducted, were selected. The strategies, Immediately, Strengthen and Empower Existing Sales Force, Focus Restructure and Improve Sales Telemarketing were brought down to the implementation level, with focus on specific plan of actions and cost benefit analysis. It was concluded that the bottom line is that the only way the company will survive is if the working capital is restored to a level that the key operational-level recommendations outlined in this study can be effectively implemented in their full scale.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Beaute Mondiale; Direct selling; Marketing; System design